A new war on cancer : the unlikely heroes revolutionizing prevention - Marusic, Kristina (Island Press, 2023)
"For more than fifty years, we have been waging, but not winning, the war on cancer. We're better than ever at treating the disease, yet cancer still claims the lives of one in five men and one in six women in the US. The astonishing news is that up to two-thirds of all cancer cases are linked to preventable environmental causes. If we can stop cancer before it begins, why don't we? That was the question that motivated Kristina Marusic's revelatory inquiry into cancer prevention. In searching for answers, she met remarkable doctors, scientists, and advocates who are upending our understanding of cancer and how to fight it. They recognize that we will never reduce cancer rates without ridding our lives of the chemicals that increasingly trigger this deadly disease. Most never imagined this role for themselves. One scientist grew up without seeing examples of Indian-American women in the field, yet went on to make shocking discoveries about racial disparities in cancer risk. Another leader knew her calling was children's health, but realized only later in her career that kids can be harmed by invisible pollutants at their daycares. Others uncovered surprising links between cancer and the everyday items that fill our homes and offices. For these individuals, the fight has become personal. And it certainly is personal for Berry, a young woman whose battle with breast cancer is woven throughout these pages. Might Berry have dodged cancer had she not grown up in Oil City, Pennsylvania, in the shadow of refineries? There is no way to know for sure. But she is certain that, even with the best treatment available, her life was changed irrevocably by her diagnosis. Marusic shows that, collectively, we have the power to prevent many cases like Berry's. The war on cancer is winnable--if we revolutionize the way we fight"--Publisher's description.